Pemanfaatan Video Youtube untuk Meningkatkan Keterampilan Mendengarkan Bahasa Jerman - Nainggolan, Laura Hotmauli; Sitinjak, Febyola Angelika; Rajagukguk, Yuni Kristina; Sari, Risnovita (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explain the use of YouTube videos as a learning tool to improve German listening skills (Hörverstehen) among students. The method applied in this study is qualitative with a descriptive approach to explore the experiences, views, and reactions of students and teachers regarding the use of YouTube videos in learning. The research subjects were selected purposively from students taking German lessons and experiencing difficulties in listening skills. Data collection techniques included observation of the learning process, in-depth interviews, and documentation of teaching materials and student reflections. The data analysis method used was thematic analysis, which includes the stages of data reduction, data presentation, and drawing conclusions, to identify thematic patterns that emerged from the qualitative data. The research findings indicate that the use of YouTube videos has positive impacts, such as improving comprehension of native speaker conversations, expanding vocabulary, increasing learning motivation, and providing access to flexible, independent learning; however, there are several challenges such as variations in the quality of the materials and the need for teacher intervention to make the use of videos more effective. The conclusion of this study states that YouTube is a learning resource that has the potential to improve German listening skills if selected and implemented pedagogically